2020
DOI: 10.3389/fonc.2020.01244
|View full text |Cite
|
Sign up to set email alerts
|

The Similar Effects of miR-512-3p and miR-519a-2-5p on the Promotion of Hepatocellular Carcinoma: Different Tunes Sung With Equal Skill

Abstract: Although the therapeutic methods of hepatocellular carcinoma (HCC) have made great advances, the current situation is that HCC is the common malignancy. Our previous bioinformatic study presented that two members of C19MC (mir-512-1 and mir-519a-2) acted as crucial roles in the HCC progression. In this study, we first demonstrated that the miR-512-3p and miR-519a-2-5p, which were spliced from the mir-512-1 and mir-519a-2, were the functional mature miRNAs. Meanwhile, both miR-512-3p and miR-519a-2-5p were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Although the oncogenic effect of miR-519a/522-5p has been proved in multiple cancer types, the molecular mechanism is still largely unknown. We previously demonstrated that the members of C19MC including miR-519a and miR-512 could co-target the downstream MAPK pathway and promote invasion in HCC [31,32]. Tu et al [27] found that miR-519a promoted colony formation, proliferation and cell cycle progression in HCC cell lines by targeting PTEN/PI3K/AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Although the oncogenic effect of miR-519a/522-5p has been proved in multiple cancer types, the molecular mechanism is still largely unknown. We previously demonstrated that the members of C19MC including miR-519a and miR-512 could co-target the downstream MAPK pathway and promote invasion in HCC [31,32]. Tu et al [27] found that miR-519a promoted colony formation, proliferation and cell cycle progression in HCC cell lines by targeting PTEN/PI3K/AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously ( Rui et al, 2020b ), the total proteins extracted from the MFC-7 and ZR-75-1 were quantified and boiled. Then, the total proteins were electrophoresed with 10% SDS-PAGE gel (FD341-100, Fudebio, China) and transferred onto equilibrated polyvinylidene-difluoride membranes.…”
Section: Methodsmentioning
confidence: 99%
“…miRNA-512 may play one of the crucial roles in HCC progression, being significantly upregulated in human HCC samples and HCC cell lines. Along with miRNA-519, it targets tumor suppressors MAP3K2 and MAP2K4, and the integration of these two miRNAs into the AJCC staging system significantly improved the accuracy of the prediction of HCC recurrence [100]. Some of these miRNAs, such as miRNA-518b, miRNA-549, miRNA-2277, and miRNA-2355, are rarely mentioned in the context of liver cancer development, and their role in this process is yet to be elucidated.…”
Section: Differential Expression Of Mirnas In Hccmentioning
confidence: 99%